If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8t + 9 = 25 Reorder the terms: 9 + 8t = 25 Solving 9 + 8t = 25 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 8t = 25 + -9 Combine like terms: 9 + -9 = 0 0 + 8t = 25 + -9 8t = 25 + -9 Combine like terms: 25 + -9 = 16 8t = 16 Divide each side by '8'. t = 2 Simplifying t = 2
| 5(x+6)=2(x+27) | | 18-30=6z | | 3a=5a+80 | | x+(-2)=-66 | | 12t-5=9t+14 | | 3(x-9)=13-x | | 112-4x=23x+16 | | -4m+2(6m+1)=23+m | | -108+x=-5x+42 | | 5x+x+(4x-16)=180 | | 2x+6=1.75x+6 | | 2x+6=12-7x | | x^2-8=7x | | 78-4x=2x+12 | | 5b+11-4b=56 | | -9p-5=93 | | e^2x=57 | | 6(5a-1)(3a+1)=0 | | 3t/5-6=t/12 | | 4(x-3)=x+3 | | (7+w)(2w+9)=0 | | 10b+9-3b=4 | | 10-8x=36-15x | | x-67=-10x+131 | | 10+2(x+2)=20 | | -7(n+7)=-9-2n | | s^2-3s=0 | | 9x^4-144x^2= | | x^2-90-3=0 | | 163-6x=6x+7 | | 3t(7t+4)= | | 2(3x+2)=5(x+2) |